Unexpected Role of MPO-Oxidized LDLs in Atherosclerosis: In between Inflammation and Its Resolution - Cecilia Tangeten; Karim Zouaoui Boudjeltia; Cedric Delporte; Pierre Van Antwerpen; Keziah Korpak (MDPI AG, 2022)
Inflammation and its resolution are the result of the balance between pro-inflammatory and pro-resolving factors, such as specialized pro-resolving mediators (SPMs). This balance is crucial for plaque evolution in atherosclerosis, a chronic inflammatory disease. Myeloperoxidase (MPO) has been related to oxidative stress and atherosclerosis, and MPO-oxidized low-density lipoproteins (Mox-LDLs) have specific characteristics and effects. They participate in foam cell formation and cause specific reactions when interacting with macrophages and endothelial cells. They also increase the production of intracellular reactive oxygen species (ROS) in macrophages and the resulting antioxidant response. Mox-LDLs also drive macrophage polarization. Mox-LDLs are known to be pro-inflammatory particles. However, in the presence of Mox-LDLs, endothelial cells produce resolvin D1 (RvD1), a SPM. SPMs are involved in the resolution of inflammation by stimulating efferocytosis and by reducing the adhesion and recruitment of neutrophils and monocytes. RvD1 also induces the synthesis of other SPMs. In vitro, Mox-LDLs have a dual effect by promoting RvD1 release and inducing a more anti-inflammatory phenotype macrophage, thereby having a mixed effect on inflammation. In this review, we discuss the interrelationship between MPO, Mox-LDLs, and resolvins, highlighting a new perception of the role of Mox-LDLs in atherosclerosis.